2017
DOI: 10.1038/npp.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate in Pediatric Obsessive-Compulsive Disorder and Response to Cognitive-Behavioral Therapy: Randomized Clinical Trial

Abstract: Cognitive-behavioral therapy (CBT) is effective for pediatric obsessive-compulsive disorder (OCD), but non-response is common. Brain glutamate (Glu) signaling may contribute to OCD pathophysiology and moderate CBT outcomes. We assessed whether Glu measured with magnetic resonance spectroscopy (MRS) was associated with OCD and/or CBT response. Youths aged 7-17 years with DSM-IV OCD and typically developing controls underwent 3 T proton echo-planar spectroscopic imaging (PEPSI) MRS scans of pregenual anterior ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Importantly, structural predictors could be combined with additional measures to improve treatment prediction in the future. For example, data suggest that baseline glutamate in the ACC predicts CBT response in youth (O'Neill et al, 2017). The combination of our multimodal structural measures did not improve prediction, likely because these measures were themselves colinear.…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, structural predictors could be combined with additional measures to improve treatment prediction in the future. For example, data suggest that baseline glutamate in the ACC predicts CBT response in youth (O'Neill et al, 2017). The combination of our multimodal structural measures did not improve prediction, likely because these measures were themselves colinear.…”
Section: Discussionmentioning
confidence: 87%
“…Participating youth were drawn from one of three clinical research protocols [3436]. Each of these studies was approved by the university institutional review board, and all youth completed assent and primary caregivers completed consent prior to initiation of any research procedures.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14] Recent studies on both pediatric and adult OCD patients demonstrated a link between the response to fear-extinction during cognitive-behavioral therapy and glutamate levels. [15][16][17] However, establishing a clear relation between glutamatergic dysfunction and OCD and understanding its exact functional meaning, is not an easy task, for several reasons. Firstly, glutamatergic neurons are present in almost all brain circuitries and are therefore difficult to specifically localize a glutamatergic dysfunction in a specific brain area.…”
Section: Glutamatergic Agents In Ocdmentioning
confidence: 99%